Mitochondrial Metagenomics Reveals the Ancient Origin and Phylodiversity of Soil Mites and Provides a Phylogeny of the Acari. (31st October 2019) - Arribas, Paula; Andújar, Carmelo; Moraza, María Lourdes; Linard, Benjamin; Emerson, Brent C; Vogler, Alfried P
Abstract: High-throughput DNA methods hold great promise for phylogenetic analysis of lineages that are difficult to study with conventional molecular and morphological approaches. The mites (Acari), and in particular the highly diverse soil-dwelling lineages, are among the least known branches of the metazoan Tree-of-Life. We extracted numerous minute mites from soils in an area of mixed forest and grassland in southern Iberia. Selected specimens representing the full morphological diversity were shotgun sequenced in bulk, followed by genome assembly of short reads from the mixture, which produced >100 mitochondrial genomes representing diverse acarine lineages. Phylogenetic analyses in combination with taxonomically limited mitogenomes available publicly resulted in plausible trees defining basal relationships of the Acari. Several critical nodes were supported by ancestral-state reconstructions of mitochondrial gene rearrangements. Molecular calibration placed the minimum age for the common ancestor of the superorder Acariformes, which includes most soil-dwelling mites, to the Cambrian–Ordovician (likely within 455–552 Ma), whereas the origin of the superorder Parasitiformes was placed later in the Carboniferous-Permian. Most family-level taxa within the Acariformes were dated to the Jurassic and Triassic. The ancient origin of Acariformes and the early diversification of major extant lineages linked to the soil are consistent with a pioneering role for mites in building the earliest terrestrial ecosystems.